2023
DOI: 10.1039/d2fo03331c
|View full text |Cite
|
Sign up to set email alerts
|

Berberine hydrochloride alleviates imatinib mesylate – induced cardiotoxicity through the inhibition of Nrf2-dependent ferroptosis

Abstract: The underlying mechanisms of protective effects of Ber on IMA-induced cardiotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Berberine is mainly extracted from the stem and root of Coptidis Rhizoma and has been widely used to treat intestinal inflammation [ 35 , 36 ]. Song et al indicated that berberine potentially protected against imatinib mesylate-induced cardiotoxicity by inhibiting Nrf2-dependent ferroptosis [ 37 ]. Berberine inhibited ferroptosis by reducing ROS generation and lipid peroxidation in cardiac cells [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Berberine is mainly extracted from the stem and root of Coptidis Rhizoma and has been widely used to treat intestinal inflammation [ 35 , 36 ]. Song et al indicated that berberine potentially protected against imatinib mesylate-induced cardiotoxicity by inhibiting Nrf2-dependent ferroptosis [ 37 ]. Berberine inhibited ferroptosis by reducing ROS generation and lipid peroxidation in cardiac cells [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Nrf2 activation plays a neuroprotective role in neurological diseases such as Parkinson’s disease ( Bento-Pereira and Dinkova-Kostova, 2021 ) and multiple sclerosis ( Montes Diaz et al, 2018 ). Nrf2 can regulate glucose uptake and metabolism of neurons ( Esteras et al, 2023 ), autophagy ( Li et al, 2021 ), ferroptosis ( Song et al, 2023 ), inflammation ( Wang J. et al, 2023 ), mitochondrial function ( Jamwal et al, 2021 ), and promote energy metabolism ( Esteras et al, 2023 ), which helps to maintain the health and survival of neurons. For example, CMPB can improve learning and memory impairment caused by fatigue by regulating PI3K/NRF2/HO-1 signal pathway, scavenging free radicals and fatigue metabolites, increasing the content of glycogen and regulating the content of central neurotransmitters in the body ( Bai et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many traditional Chinese medicine monomers and preparations have shown good effects on inhibiting ferroptosis by targeting NRF2-related pathway. Berberine hydrochloride increased cell viability and MMP by inhibiting NRF2 [ 205 ] or by reducing ROS generation and lipid peroxidation [ 206 ], showing a good inhibitory effect on ferroptosis. Britanin can alleviate ferroptosis by activating AMPK/GSK3β/NRF2 signaling pathway and up-regulating GPX4 [ 207 ].…”
Section: Targeted Interventions and Prospectsmentioning
confidence: 99%